2008
DOI: 10.1097/bpo.0b013e318164ee43
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Four Different Fixation Techniques for Pediatric Tibial Eminence Avulsion Fractures

Abstract: There was not a clear biomechanical advantage to performing any particular fixation method in this study. This suggests that the surgeon can use their clinical judgment and experience to determine the fixation technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 12 publications
1
48
2
Order By: Relevance
“…Successful results have been reported with both methods of fixation. [2][3][4][9][10][11][12][13] The results of biomechanical studies comparing suture and screw fixation are mixed, [14][15][16][17] and few clinical studies directly compare these two methods of fixation. 18,19 The purpose of this review is to provide a synthesis of the literature regarding the outcome of nonoperatively and operatively treated displaced tibial eminence fractures.…”
Section: Introductionmentioning
confidence: 98%
“…Successful results have been reported with both methods of fixation. [2][3][4][9][10][11][12][13] The results of biomechanical studies comparing suture and screw fixation are mixed, [14][15][16][17] and few clinical studies directly compare these two methods of fixation. 18,19 The purpose of this review is to provide a synthesis of the literature regarding the outcome of nonoperatively and operatively treated displaced tibial eminence fractures.…”
Section: Introductionmentioning
confidence: 98%
“…5) metal screws [82][83][84][85], bioabsorbable nails [86], Kirschner wires [36,41,43,76], or suture anchors [87,88]. Several reports have found that screws can actually weaken the small fragment or cause comminution [78] and thus recommend suture fixation, which has demonstrated similar or improved strength profiles [89][90][91]. Typically some sort of visualization is required to reduce the fracture fragment as there is a high likelihood of entrapment of the intermeniscal ligament or the anterior horn of the medial or lateral meniscus [12,84].…”
Section: Tibial Eminence Fracturementioning
confidence: 99%
“…7 Tibial eminence fractures Tibial eminence fractures are most commonly seen in children aged 8e17 years and represent 14% of anterior cruciate ligament injuries. 8 Classified by Meyers and McKeevers into 3 types based on degree of displacement and position of the fracture fragment, most commonly they are of the displaced type. 9 The injury is usually sustained during sporting activities, particularly football or skiing, and is associated with bone bruising typical of that occurring with an ACL rupture in 90% of cases, suggesting a similar mechanism of injury.…”
Section: Tibial Tuberosity Fracturesmentioning
confidence: 99%
“…Although both have similar biomechanical properties, suture fixation has been shown to undergo deformation with cyclical loading, which may result in postoperative ACL laxity. 8 The main disadvantage of screw fixation is the requirement to cross the physis, and the associated risk of growth arrest.…”
Section: Tibial Tuberosity Fracturesmentioning
confidence: 99%